TERTIARY ESL STUDENTS’ PERCEPTIONS ON THE ACQUIRED AND USED LANGUAGES ( A CASE STUDY AT UNIVERSITY LEVEL) - Fauzi, Rachmi Hasan; Hakim, Luqman (Universitas Muhammadiyah Tangerang, 2022)
Abstract Language attitudes towards languages acquired and use in young generation is the main issue of this study, This study aimed to answer the following questions; 1. How do tertiary ESL students perceive their language acquisition and use? a. How do they rate their proficiency in each language? b.What language(s) are dominantly used ? for what purposes? In what settings? c.What do they think of their heritage language and its maintenance? 2. What efforts have they done to maintain their heritage languages and/or languages they acquired and use? a.What factors that motivate them to maintain their heritage languages and/or languages they acquired and use? b.What are the constraints in their efforts to maintain the languages? c. What strategies have they adopted in maintaning their heritage language?. The methodology used in this study is qualitative which employs 65 students of English department at fifth semester. The result of this study, all participants have positive attitudes towards the languages they acquired and used. Most of them perceive that they have to maintain their heritage languages, and some of them have done some efforts in maintaining it. Moreover, they also have the same problems in persevere their heritage language, that the languages are rarely used. So, in conclusion the students know that they have to something in maintaining the languages they have acquired and use, however, they did less action.Key words: Heritage language, Language attitude, Language acquisition, Language use, Perceptions